Developments in X-Ray Tomography XIII 2021
DOI: 10.1117/12.2597926
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory-based phase and absorption tomography for micro-imaging of annual layers in human tooth cementum, paraffin-embedded nerve and zebrafish embryo

Abstract: Synchrotron radiation-based tomography yields the micro-anatomical features in human and animal tissues without physical slicing. Recent advances in instrumentation have made laboratory-based phase tomography feasible. We compared the performance of three cutting-edge laboratory systems benchmarked by synchrotron radiation-based tomography for three specimens. As an additional criterion, the user-friendliness of the three microtomography systems is considered. The three tomography systems-SkyScan 2214 (Bruker-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…The minimum number of occurrences of a term was set to four, and in total 140 terms were used based on these studies [ 11 , 31 , 39 , 56 , 57 , 77 , 78 , 89 , 90 , 121 , 169 , 170 , 171 , 172 , 173 , 175 , 193 , 195 , 247 , 266 , 286 , 294 , 299 , 303 , 304 , 305 , 306 , 307 , 308 , 309 , 310 , 311 , 312 , 313 , 314 , 315 , 316 , 317 , 318 , 319 , 320 , 321 , 322 , 323 , 324 , 325 , 326 , 327 , 328 , 329 , 330 , 331 ...…”
Section: Figurementioning
confidence: 99%
“…The minimum number of occurrences of a term was set to four, and in total 140 terms were used based on these studies [ 11 , 31 , 39 , 56 , 57 , 77 , 78 , 89 , 90 , 121 , 169 , 170 , 171 , 172 , 173 , 175 , 193 , 195 , 247 , 266 , 286 , 294 , 299 , 303 , 304 , 305 , 306 , 307 , 308 , 309 , 310 , 311 , 312 , 313 , 314 , 315 , 316 , 317 , 318 , 319 , 320 , 321 , 322 , 323 , 324 , 325 , 326 , 327 , 328 , 329 , 330 , 331 ...…”
Section: Figurementioning
confidence: 99%
“…They found that the bioapatite in the cone walls and wedges is oriented to resist lateral and axial deflections, respectively. Based on an awarded conference paper, 5 the article lead-authored by A. Migga systematically compared the performance of three cutting-edge laboratory systems for three specimens namely, paraffin-embedded zebrafish larva, bare archaeological human tooth, and paraffin-embedded porcine nerve ( https://doi.org/10.1117/1.JMI.9.3.031507 ). These systems include SkyScan 2214 (Bruker-microCT, Kontich, Belgium), Exciscope prototype (Stockholm, Sweden), and Xradia 620 Versa (Zeiss, Oberkochen, Germany).…”
mentioning
confidence: 99%